18F-FDG micro-PET/CT for intra-operative margin assessment during breast-conserving surgery. Issue 5 (2nd September 2020) - Göker, Menekse; Marcinkowski, Radosław; Van Bockstal, Mieke; Keereman, Vincent; Van Holen, Roel; Van Dorpe, Jo; Vandenberghe, Stefaan; Brans, Boudewijn; Depypere, Herman; Van den Broecke, Rudy
Abstract: Rationale: Positive surgical margins for invasive breast cancer (BC) treated with breast-conserving surgery (BCS) are defined as ink on tumor. The rate of positive margins is approximately 20%, since a time- and cost-effective method for margin assessment is lacking. In this study, we investigated margin status by intra-operative imaging using high-resolution 18 F-fluoro-deoxyglucose (FDG) positron emission tomography (PET) and X-ray computed tomography (CT). Methods: Twenty patients were enrolled and received 4 MBq/kg of FDG prior to surgery. Intra-operative imaging of the specimens was performed by the MOLECUBES β-CUBE (PET) and X-CUBE (CT). Margin status was assessed by three surgeons and compared with an algorithm. The sensitivity and specificity were calculated by using histopathological assessment as a gold standard. Results: A region with high FDG uptake was visualized in all specimens. Automated analysis showed a sensitivity of 90%, a specificity of 60%, and an area under the curve (AUC) of 0.86 after ROC analysis. Margin assessment by the surgeons resulted in a mean sensitivity and specificity of 79% and 72%, respectively. Conclusions: This proof-of-concept study demonstrates that high-resolution FDG-PET/CT can facilitate intra-operative margin assessment during BCS. This technique achieves good sensitivity and specificity and may therefore reduce re-operation rates in the future.